Experience of Implementation of an Organizational and Methodological Approach to the Description and Standardization of Treatment and Diagnostic Processes in N.V. Sklifosovsky Research Institute for Emergency Medicine - N. S. Fomenko; A. Y. Perminov; S. S. Petrikov (Неотложная медицинская помощь, 2021)
Currently, the issues of improving the quality of medical care and the effectiveness of management are in the focus of attention of heads of medical organizations. Obviously, for the successful management of any complex object, it is necessary to understand the principles of its operation and have a formalized description (model).This article presents the experience of systemic implementation of the organizational and methodological approach developed by the authors to the description and standardization of the treatment and diagnostic processes of a multidisciplinary hospital.When writing the work, the methods of system analysis and synthesis were used. Analyzed and systematized the successful experience of the N.V. Sklifosovsky Research Institute for Emergency Medicine on the introduction of the developed organizational and methodological approach into the current activities of a medical institution, as well as the results of its approbation in more than 270 complex medical and diagnostic processes, surgical interventions, active methods of treatment, instrumental and laboratory diagnostics.The article defines the most important principles for the formation of small groups, the basic values underlying their work, the main motivational factors for the participation of doctors, as well as critical factors for the success of the implementation of the organizational and methodological approach. The experience of its phased implementation is considered: from the processes of the admission department to the processes of medical and intensive care departments; as well as implementation features in the description of diagnostic profile processes.Based on the results of the implementation of the organizational and methodological approach at the N.V. Sklifosovsky Research Institute for Emergency Medicine, a conclusion was made about its universality and applicability for any medical institution.In the conclusion of the article, recommendations are formulated for the systemic organization of implementation in a medical institution of the organizational and methodological approach developed by the authors to the description and standardization of treatment and diagnostic processes.